MEDIA KOMUNITAS DAN PRODUKSI BUDAYA DEMOKRASI - Annis Azhar Suryaningtyas; Sika Nur Indah (Jurnal Komunikasi dan Budaya, 2021)
Talking about the media cannot be separated from society and culture. The media has an influence on the formation of culture in society. This study aims to determine how the SPEAKER Kampung as a community media played a role in producing a democratic culture in forms of freedom of speech and ways to express for the people of East Lombok. This community media was chosen because it exists in the midst of the development of mainstream media in the digital era. The research was conducted using qualitative methods through observation of journalistic products and in-depth interviews with citizen journalists in the community. The sample was selected by purposive sampling technique and data analysis using interactive analysis model of Miles and Hubermas. As a result, the SPEAKER Kampung as a community media was able to take a role as an alternative media in the community. Production practice is constructed by four elements: 1) the strength of the habitus of each citizen journalist volunteer as a production actor, 2) the strong role of cultural capital and symbolic capital, 3) the availability of an arena where alternative media production practices can grow, 4) and the authority over production results. This production practice then mediates the formation of a democratic culture. The results of this study are expected to contribute in providing an overview of how community media is able to be part of shaping a democratic culture in the society around the community media area. Keywords: cultural production, community media, democratic culture